2004
DOI: 10.1159/000080462
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Low-Density Lipoprotein Receptor Activity by Estrogens and Phytoestrogens in a HepG2 Cell Model

Abstract: Background/Aims: Estrogen treatment is thought to lower low-density lipoprotein (LDL) cholesterol levels by increasing clearance through hepatic LDL receptors. This study aimed to determine the effect of estrogens and phytoestrogens on LDL receptor activity in a human hepatoma cell line, HepG2. Methods: HepG2 cells in culture were incubated for 24 h with estrogen or phytoestrogen and LDL receptor activity was measured by examining the cellular binding of colloidal gold-labelled LDL. Results: 17β-Estradiol sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 79 publications
1
20
2
1
Order By: Relevance
“…The two major phytoestrogenic lignans detected in human tissue are enterolactone and enterodiol, which are derived from plant lignans metabolised by colonic microflora. Enterodiol and enterolactone have been shown to display weak estrogenic and anti-estrogenic activity [45,46], as well as antioxidant activity [47], although we have found enterodiol to have a greater ability to inhibit LDL oxidation than enterolactone [48]. In the present study, these phytoestrogenic lignans had little influence upon LDL uptake into macrophages, but significantly reduced macrophage Lp(a) uptake, with enterodiol being the most effective.…”
Section: Discussioncontrasting
confidence: 66%
“…The two major phytoestrogenic lignans detected in human tissue are enterolactone and enterodiol, which are derived from plant lignans metabolised by colonic microflora. Enterodiol and enterolactone have been shown to display weak estrogenic and anti-estrogenic activity [45,46], as well as antioxidant activity [47], although we have found enterodiol to have a greater ability to inhibit LDL oxidation than enterolactone [48]. In the present study, these phytoestrogenic lignans had little influence upon LDL uptake into macrophages, but significantly reduced macrophage Lp(a) uptake, with enterodiol being the most effective.…”
Section: Discussioncontrasting
confidence: 66%
“…Menopausal statement due to reduced estrogen secretion is associated with hyperlipidemia, which is defined by increased level of cholesterol, TG, LDL, and decreased level of HDL (17). It has been demonstrated that estrogen has a physiological role in lowering cholesterol through upregulation of hepatic LDL receptor, consequently leading to an enhanced clearance of blood cholesterol (18).…”
Section: Discussionmentioning
confidence: 99%
“…As IF in blood are associated with circulating lipoproteins, predominantly with LDL , they may be able to directly affect receptors involved in LDL‐uptake, in particular LDLR and CD36. In cell culture experiments, the IF genistein stimulated LDLR expression, and an increased LDLR activity was shown in the presence of the IF daidzein . Therefore, IF could have an impact on LDLR expression and activity as it has been shown for estradiol and by this mechanism may reduce serum LDL‐chol.…”
Section: Introductionmentioning
confidence: 75%